Taxonomy of the genus Parasycorax Duckhouse (Diptera, Psychodidae, Sycoracinae), with description of a new species from Brazil - Santos, Claudiney Biral Dos; Ferreira, Adelson Luiz; Bravo, Freddy (Zootaxa, 2009)
The genus Parasycorax Duckhouse, 1972 is reviewed and a key is provided for the four known species: Parasycorax satchelli (Barretto, 1956) from Brazil, P. filipinae (Quate, 1965) from Philippines, Parasycorax utriensis (Bejarano, Duque & Vélez, 2008) comb. n. from Colombia, and Parasycorax bidentis Santos, Ferreira & Bravo sp. n. from Brazil. A diagnosis of the type species of the genus is updated with observations of the specimens collected in Espírito Santo State, Brazil.